Efficacy of stage I rehabilitation of medical workers with moderate course of interstitial lung damage associated with COVID-19 - L. A. Shpagina; V. A. Drobyshev; S. A. Karmanovskaya; E. M. Loktin; I. S. Shpagin; O. S. Kotova; L. A. Panacheva; T. V. Musienko; E. A. Zaikina (Сибирский научный медицинский журнал)
Aim of the study was to evaluate the effectiveness of early rehabilitation methods for medical workers with severe or moderate lung damage caused by a new coronavirus infection, who are in intensive care units, to improve lung ventilation, gas exchange and bronchial clearance, correct muscle weakness, increase overall physical endurance, mobility, psycho-emotional stability.Material and methods. We examined 53 COVID-19 women with moderate lung injury at stage I of rehabilitation, divided into two groups: main (n = 31, medical personnel) and control (n = 22, working outside of contact with pulmotropic risk factors, including no risk of SARS-CoV-2 infection). Early rehabilitation was carried out in the intensive care unit and in the infectious diseases hospital of City Clinical Hospital No. 2, for patients with COVID-19 rehabilitation plan was drawn up in accordance with temporary guidelines for the medical rehabilitation of a new coronavirus infection.Results and discussion. It was established, that rehabilitation in the conditions of the intensive care unit and the specialized department can significantly reduce the severity of dyspnea, anxiety and depression, positively affects the increase in exercise tolerance, and helps to reduce the activity of systemic inflammation. In patients who have industrial contact with patients with COVID-19, the effectiveness of rehabilitation measures is lower than in the comparison group.Conclusions. To increase the effectiveness of stage I of the rehabilitation of medical workers with COVID-19 and lung damage, it is necessary to conduct more intensive and longer rehabilitation than indicated in the current guidelines.